Peptide Amphiphile Nanogel as an Improved BMP-2 Carrier for Spinal Arthrodesis. Issue 1 (April 2016) - Hsu, Wellington; Weiner, Joseph; Chun, Danielle; Lee, Sungsoo; McClendon, Mark; Freshman, Ryan; Cook, Ralph; Schallmo, Michael; Singh, Sameer; Yun, Jonghwa; Yun, Chawon; Stupp, Samuel; et al.
Introduction: Advances in biologics have led to improvements in spine fusion rates, but a commercially available bone graft substitute that elicits high bony fusion rates with minimal adverse effects is yet to be developed. Recombinant human bone morphogenetic protein-2 (rhBMP-2) is FDA-approved for delivery on an absorbable collagen sponge (ACS), and promotes spine fusion at rates of > 90% in humans. However, the supraphysiologic dose required to elicit these high rates of fusion can lead to serious complications. In prior work, we found that nanofiber scaffolds composed of self-assembling peptide amphiphiles (PA) are improved carriers relative to ACS, with the ability to reduce the dose of exogenous growth factor necessary for spine arthrodesis by a factor of 10. We have also shown that assembling a PA nanogel on ACS improves the handling properties of the nanogel without compromising bioactivity. The purpose of this study was to develop a novel PA-based growth-factor carrier that would further reduce the amount of rhBMP-2 necessary to achieve high spine fusion rates, while simultaneously improving ease-of-delivery. We hypothesized that assembling a carboxyl-rich E3-PA nanogel with a slurry of Type I collagen particles would yield a malleable paste with improved growth factor delivery in a spine fusion setting. Material and Methods: Female Sprague-Dawley rats underwent L4-L5 posterolateral spine fusion (PLF) with one of two experimental scaffolds: 1) E3PA-collagen slurry scaffold; or 2) E3PA/ACS. Scaffolds were preloaded with either saline or 100 ng rhBMP-2 (per animal). A negative comparative control group received ACS + 100 ng rhBMP-2. Bone regeneration and spine fusion were assessed using radiographs, fusion scoring, microCT imaging, and histology. Fusion scores were determined by blinded manual palpation using an established scoring system: 0 = no bridging bone, 1 = unilateral bridging, and 2 = bilateral bridging bone. Spines with an average score of ≥ 1.0 were considered successfully fused. Results: When preloaded with 100 ng rhBMP-2, the E3PA/collagen slurry elicited a significantly higher mean fusion score relative to both equivalently pre-loaded ACS ( p < 0.001) and E3PA/ACS ( p < 0.01). Successful fusion was seen in 100% of animals treated with E3PA-collagen slurry + 100 ng rhBMP-2 (12/12 animals), which was significantly higher than fusion rates of both ACS + 100 ng rhBMP-2 (0%) and E3PA + 100 ng rhBMP-2 (8%) treatment groups. Use of the E3-collagen slurry for rhBMP-2 delivery reduced the growth factor requirement by 100-fold relative to the positive control in this model (10 µg rhBMP-2/ACS, which yields a fusion rate of 100% in the rat). Conclusion: Exogenous growth factors, such as rhBMP-2, have the potential to significantly improve bony fusion rates. However, concerns regarding the safety of supraphysiologic concentrations of rhBMP-2—which are required for efficacy when delivered on ACS—make the development of improved growth factor delivery systems attractive. This study examined the growth factor delivery capacity of a PA nanogel/collagen slurry composite scaffold in a lumbar spine fusion setting. We found that delivery of rhBMP-2 using an E3PA-collagen slurry scaffold reduces the requirement for growth factor by a 100-fold relative to ACS in the rat PLF model.